PENGETAHUAN MANAJEMEN PETERNAKAN DAN PEMANFAATAN HASIL TERNAK SEBAGAI SUMBER GIZI MASYARAKAT DI KECAMATAN BARON KABUPATEN NGANJUK - Sunaryo Hadi Warsito; Oky Setyo Widodo; Shelly Wulandari (Universitas Airlangga, 2018)
The community in Kertosono Subdistrict has an average farming and trading livelihood. Almost all of the people who work as farmers have livestock that are kept as a side business or livelihood. Livestock that are kept include beef cattle, goats and sheep. The problems that arise include: The community has not fully understood how to obtain meat from the sacrifice of qurban animals with good quality. The public does not know of zoonotic diseases, and there are still not many people who know how the procedures for slaughtering livestock are good . The main objective in this community service activity is to be able to increase the knowledge and skills of the community regarding the criteria for ASUH meat (Safe, Healthy, Whole, and Halal) and appropriate handling and restraint on livestock.Abstrak